Proteomic Analysis of the Murine Liver Response to Oral Exposure to Aflatoxin B1 and Ochratoxin A: The Protective Role to Bioactive Compounds - Silvia Trombetti; Alessandra Cimbalo; Michela Grosso; Pilar Vila-Donat; Jordi Mañes; Lara Manyes (Toxins)
Aflatoxin B1 (AFB1) and Ochratoxin A (OTA) are considered the most important mycotoxins in terms of food safety. The aim of this study was to evaluate the hepatotoxicity of AFB1 and OTA exposure in Wistar rats and to assess the beneficial effect of fermented whey (FW) and pumpkin (P) as functional ingredients through a proteomic approach. For the experimental procedures, rats were fed AFB1 and OTA individually or in combination, with the addition of FW or a FW-P mixture during 28 days. For proteomics analysis, peptides were separated using a LC-MS/MS-QTOF system and differentially expressed proteins (DEPs) were statistically filtered (p < 0.05) distinguishing males from females. Gene ontology visualization allowed the identification of proteins involved in important biological processes such as the response to xenobiotic stimuli and liver development. Likewise, KEGG pathway analysis reported the metabolic routes as the most affected, followed by carbon metabolism and biosynthesis of amino acids. Overall, the results highlighted a strong downregulation of DEPs in the presence of AFB1 and OTA individually but not with the mixture of both, suggesting a synergistic effect. However, FW and P have helped in the mitigation of processes triggered by mycotoxins.